2016
DOI: 10.1093/esr/jcw027
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Integration and Youth Mental Health in Four European Countries

Abstract: The mental health of children of immigrant background compared to their majority peers is an important indicator of integration. We analyse internalizing and externalizing problems in 14-15-year-olds from England, Germany, the Netherlands, and Sweden (n ¼ 18,716), using new comparative data (Children of Immigrants Longitudinal Survey in Four European Countries). Studying more than 30 different origin countries, we find that despite potential problems with acculturation and social stress, children of immigrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 50 publications
(49 reference statements)
5
56
3
4
Order By: Relevance
“…If immigrants integrate into the destination country, we would expect to find a convergence toward the majority's health level across immigrant generations or across time spent in the destination country. Although some earlier studies suggested such a pattern (e.g., Harker, ; Montazer & Wheaton, ; Salas‐Wright et al, ), our previous analyses (Mood et al, in press) revealed no or very little convergence in the countries we examined. We have therefore included both the first (born abroad) and second (born in the host country to immigrant parents) generation in our immigrant origin groups, but we controlled for generation in our analyses (which did not alter the results).…”
Section: The Current Studycontrasting
confidence: 60%
See 3 more Smart Citations
“…If immigrants integrate into the destination country, we would expect to find a convergence toward the majority's health level across immigrant generations or across time spent in the destination country. Although some earlier studies suggested such a pattern (e.g., Harker, ; Montazer & Wheaton, ; Salas‐Wright et al, ), our previous analyses (Mood et al, in press) revealed no or very little convergence in the countries we examined. We have therefore included both the first (born abroad) and second (born in the host country to immigrant parents) generation in our immigrant origin groups, but we controlled for generation in our analyses (which did not alter the results).…”
Section: The Current Studycontrasting
confidence: 60%
“…Our review of the literature suggests that characteristics of immigrant families may constitute part of the mechanism underlying the mental health advantage of youth of immigrant background, and our overall hypothesis is that the advantage in mental health observed for children of immigrant background is reduced when these potential mediating factors are accounted for. We build on our previous work (Mood et al, in press) using the same data, where we were able to establish that immigrant–background youth have a mental health advantage in the European countries that we study. This holds for youth with origins in Africa, Latin America, Southern Europe, and the Middle East and to some extent among other Asian origin youths, but not for immigrants from Western countries or from Eastern Europe.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, Norway experiences a demographic shift and an increase in cultural diversity, and currently many children and adolescents in Norway have an immigrant background (Fandrem, Sam, & Roland, 2009;Oppedal, 2017). A country's success in integrating immigrants' children and successful adaptation of children of immigrants are vital social policy issues for many countries including Norway due to its longterm consequences for well-being of immigrant members and vitality of host countries (Mood, Jonsson, & L aftman, 2016;Motti-Stefanidi, Asendorpf, & Masten, 2012a). The better understanding of adaptation processes, hence, became a necessity for both scholars and policy-makers in the receiving countries (Berry, Phinney, Kwak, & Sam, 2006;Schiefer, M€ ollering, & Daniel, 2012).…”
Section: Introductionmentioning
confidence: 99%